Grass-mud horse: Luhmannian systems theory and internet censorship in China. Issue 5 (2nd May 2017) - Clark, Carlton; Zhang, Lei
Abstract : Purpose: This paper aims to elucidate the systemic processes underlying the enhanced information-control measures taken by the Chinese Communist Party (CCP) under the leadership of President Xi Jinping. The tightening of state information control has stimulated increasingly sophisticated methods of disseminating information on the part of professional and citizen journalists. Drawing on social systems theory as articulated by Niklas Luhmann and others, the authors frame the CCP's enhanced information-control efforts as a response to the increasing systemic complexity of Chinese journalism, which is part of a self-reproducing, self-regulating (autopoietic) global journalism system. The authors use both subtle and overt protests over Chinese censorship as evidence for the journalism system's increasing complexity and autonomy. The authors observe that levels of complexity ratchet up as the CCP and Chinese journalism counter each other's moves. Finally, the authors suggest that the increasing complexity of the CCP's information-control apparatus may be unsustainable. Design/methodology/approach: The authors ground their argument in Luhmannian social systems theory. Findings: The CCP's effort to control journalism leads to increased internal complexity in the form of huge bureaucracies that themselves must be overseen in an almost endless proliferation of surveillance. Research limitations/implications: This paper contributes to theoretical work in post-humanism. Originality/value: To the authors' knowledge, no studies have examined the tension between CCP censors and Chinese journalism from a Luhmannian systems theory perspective.